2018
DOI: 10.3390/su10061969
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of Perennial Barley for Cold Temperate Climates—Evaluation of Wild Barley Relatives as Genetic Resources

Abstract: Perennial cereal crops could limit the negative impacts of agriculture on the environment and climate change. In cold temperate climates, perennial plants must be adapted to seasonal changes and abiotic stresses, such as frost, to be able to regrow for several years. Wild crop relatives that are perennials and already adapted to cold temperate climates may provide genetic resources for breeding new perennial cereal grain crops. Barley (Hordeum vulgare) is one of the most important cereals in northern agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…H. bulbosum is considered to be the genetically closest wild perennial relative to barley. These four introgression lines harbor different segments of H. bulbosum [52,54] and they were chosen for this study since they also indicated promising performance in trials carried out by Westerbergh et al [52]. Similar to many of the wheat hybrid lines, the barley ILs did not show persistence from year 2 to year 3 in the cold winter climate (data from two sites) or the mild winter climate conditions (data from two sites).…”
Section: Barley Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…H. bulbosum is considered to be the genetically closest wild perennial relative to barley. These four introgression lines harbor different segments of H. bulbosum [52,54] and they were chosen for this study since they also indicated promising performance in trials carried out by Westerbergh et al [52]. Similar to many of the wheat hybrid lines, the barley ILs did not show persistence from year 2 to year 3 in the cold winter climate (data from two sites) or the mild winter climate conditions (data from two sites).…”
Section: Barley Derivativesmentioning
confidence: 99%
“…In comparison to the development of perennial wheat, perennial barley is at an earlier stage [52]. Barley and its wild relatives in the genus Hordeum are widespread among various climates, and barley is the cereal which is grown in the most northern agricultural areas.…”
Section: Barley Derivativesmentioning
confidence: 99%
“…[33]. The issue also includes a review focusing on species in the legume family under consideration for domestication as pulse crops [34].…”
Section: Breeding Perennial Grainsmentioning
confidence: 99%
“…Some of the species currently in early stages of evaluation include perennial grain candidates including Hordeum bulbosum, a wild perennial barley. Such a wild plant is being explored by scientists around the world for barley breeding and improvement but is also beginning to be explored for domestication as a perennial grain (Westerbergh et al, 2018). plants in a social context in order to advance pilot studies for selection and domestication; the group envisions perennial grain agroecosystems in Palestine (Tesdell et al, 2020).…”
Section: A So Cial Perennial Vis I Onmentioning
confidence: 99%